TINJAUAN TEORI SOLIDARITAS SOSIAL EMILE DURKHEIM TERHADAP PERNIKAHAN DINI DI DESA KARANGPURI SIDOARJO - Tsabitah Nurlianty Fathurrozie; Ulfa Nurul Badria; Mohammad Naufal Hilmi; Muhammad Jazil Rifqi (Universitas Islam Negeri Alauddin Makassar, 2024)
Marriage is a perfecting act of worship that can only be undertaken by couples who love each other. There are provisions before embarking on the journey of married life. In Indonesia, both partners intending to marry must be at least 18 years old. However, many couples still marry below this minimum age limit. There are numerous factors and consequences of early marriage. This writing represents an empirical legal research or sociological legal research obtained based on primary data sources and reviewed in terms of its location, which falls under field research. Data was collected through interviews and field notes. The research location was in Karangpuri village, Wonoayu Sub-district. The research findings indicate that the most influencing factors of early marriage are economic factors, low educational attainment, and cultural factors of the local community. Nevertheless, the incidence of early marriage in Karangpuri village has significantly decreased. The decline in early marriage rates in Karangpuri village is attributed to the diligent efforts of the Wonoayu KUA officials who have provided counseling on the impacts of early marriage. Early marriage, as a form of organic solidarity in the context of Emile Durkheim's theory, encompasses aspects of role specialization, economic dependency, and the formation of social relationships. Keywords: Early Marriage, Social Solidarity Theory, Marriage Law.